2014
DOI: 10.1007/s13594-014-0180-7
|View full text |Cite
|
Sign up to set email alerts
|

Organic acids profiles in lactose-hydrolyzed yogurt with different matrix composition

Abstract: International audienceThe composition of the dairy matrix used in yogurt manufacture could influence the metabolic activity of yogurt starter and the compounds produced during fermentation. In this way, the lactose hydrolysis with a β-galactosidase enzyme and the supplementation with dairy powders to obtain different types of delactosed yogurts for lactose-intolerant people modifies the milk base composition. In this work, we studied the influence of the addition of different doses of β-galactosidase and level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 36 publications
8
34
1
Order By: Relevance
“…Recently, Vénica et al . () studied the carbohydrate profiles in drinkable and stirred yogurts made with and without added β‐galactosidase. They observed that starter cultures metabolise rapidly the glucose to growth as this sugar was not detected in unhydrolysed fresh yogurts, whereas in delactozed yogurts, there was an overproduction of glucose that lactic acid bacteria could not fully use.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Vénica et al . () studied the carbohydrate profiles in drinkable and stirred yogurts made with and without added β‐galactosidase. They observed that starter cultures metabolise rapidly the glucose to growth as this sugar was not detected in unhydrolysed fresh yogurts, whereas in delactozed yogurts, there was an overproduction of glucose that lactic acid bacteria could not fully use.…”
Section: Resultsmentioning
confidence: 99%
“…Lactose and acid lactic content in yogurts was determined during fermentation and storage by HPLC method according to Vénica et al . (). Analyses were performed in duplicate.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Summarizing, the inclusion of β ‐galactosidase enzyme in yogurt making changes the carbohydrate pattern in the matrix; hence different relative proportions of lactose, glucose, galactose and GOS are found during the process. This different sugar profile could affect the metabolic activity of cultures and consequently the production of derived compounds as well as some physicochemical characteristics of the product . Besides, the extent of these changes can be influenced by the matrix composition.…”
Section: Introductionmentioning
confidence: 99%